Determinants for Effective Nutritional Counselling on Prognosis of Moderate Acute Malnutrition in Paediatric HIV/AIDS Positive Patients Conducted at Hoima Regional Referral Hospital, Uganda - Abigaba, Emily; Aheisibwe, Irene (East African Journal of Health and Science, 2023)
This study evaluated the determinants of effective nutritional counselling on the prognosis of moderate acute malnutrition in Paediatric HIV/AIDS patients at Hoima Regional Referral Hospital. This study used pre- and post-study design, which measured the occurrence of an outcome of interest using specific values in a group of participants before and after the intervention; it was conducted among 157 paediatric HIV/AIDS patients at Hoima RRH, western Uganda. Data were obtained from all the participants using a questionnaire, and focus group discussion was analysed using Stata 17. The findings reveal that of the 157 paediatric HIV/AIDS patients studied, 67.5% improved after nutritional counselling. Paediatric HIV/AIDS patients aged ≥ 60 months (p = 0.009), caretakers whose occupations other than peasantry (p = 0.021), and attendance to ≥ 3 nutritional counselling sessions (p = 0.004) were associated with a higher likelihood of improvement after nutritional counselling with a significant increase in Body Mass Index of (p = 0.007). Thus, the majority of Paediatric HIV/AIDS patients indicated a significant improvement in prognosis after nutritional counselling and being aged ≥ 60 months, having an attendance of ≥ 3 sessions and having a caretaker’s occupation other than peasantry determined the effectiveness of nutritional counselling. The study concludes that there is a need to routinely refer Paediatric HIV/AIDS patients with moderate acute malnutrition for nutritional counselling